The Effect of Islamic Bank Financing Performance on the Achievement of Maqashid Shariah and Economic Sustainability in Indonesia - Duduh Sujana (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study examines the effect of Islamic bank financing performance on the achievement of Maqashid Shariah and economic sustainability in Indonesia during the 2020–2024 period. The study is grounded in the view that Islamic banking should not be oriented solely toward profitability, but must also fulfill broader social, ethical, and developmental objectives in accordance with Islamic principles. A quantitative approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The analysis was based on secondary data collected from 10 Islamic commercial banks in Indonesia, annual financial reports, Financial Services Authority statistics, and Bank Indonesia publications. Financing performance was measured using indicators such as Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), Return on Assets (ROA), and Operational Efficiency Ratio (BOPO), while Maqashid Shariah was represented by the dimensions of education, justice, and public welfare, and economic sustainability was reflected in green financing, financial inclusion, and sustainable economic contribution. The results show that financing performance has a positive and significant effect on the achievement of Maqashid Shariah. Furthermore, Maqashid Shariah has a positive and significant effect on economic sustainability. The findings also confirm that Maqashid Shariah mediates the relationship between financing performance and economic sustainability. These results imply that the effectiveness of Islamic bank financing should be assessed not only through financial indicators but also through its contribution to social welfare and sustainable economic development. This study contributes to the literature on Islamic banking by integrating performance, maqashid orientation, and sustainability into a single analytical framework and offers practical implications for regulators and Islamic banking institutions in strengthening value-based financial intermediation. Keywords: Islamic bank financing performance, Maqashid Shariah, economic sustainability, Islamic banking, SEM-PLS, Indonesia